2022
DOI: 10.3390/molecules27072270
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Capability of Clove Flower Extract (CFE) in Streptozotocin-Induced (STZ-Induced) Diabetic Rat Wounds Infected with Multidrug Resistant Bacteria

Abstract: Treatment of diabetic foot ulcer (DFU) is of great challenge as it is shown to be infected by multidrug resistant bacteria (MDR bacteria). Sixty four bacterial isolates were isolated from DFU cases; antibiotic susceptibility tests were carried out for all of them. One bacterial isolate (number 11) was shown to resist the action of 8 out of 12 antibiotics used and was identified by both a Vitek-2 system and 16S rRNA fingerprints as belonging to Proteus mirabilis, and was designated Proteus mirabilis LC587231 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…37 Excessive secretion of TNF-α, IL-1β, and IL-6 promotes tissue damage, interferes with proliferation and maturation, and thus delays healing of diabetic wounds. 38 In this study, the levels of TNF-α, IL-1β, and IL-6 were found to be considerably higher in the diabetic rat model than that in the controls. Studies have shown that a variety of dressings promote wound healing by inhibiting these inflammatory factors levels.…”
Section: Discussionmentioning
confidence: 49%
“…37 Excessive secretion of TNF-α, IL-1β, and IL-6 promotes tissue damage, interferes with proliferation and maturation, and thus delays healing of diabetic wounds. 38 In this study, the levels of TNF-α, IL-1β, and IL-6 were found to be considerably higher in the diabetic rat model than that in the controls. Studies have shown that a variety of dressings promote wound healing by inhibiting these inflammatory factors levels.…”
Section: Discussionmentioning
confidence: 49%
“…The increase in wound healing markers, such as TGF-β, Coli1, MMP-9, proliferating cell nuclear antigen (PCNA), and fibronectin, were indications of wound healing in this study. 22 The TGF-β is known to have pleiotropic effects on wound healing through the regulation of cell proliferation, differentiation, extracellular matrix production, and immune response modulation. An increased level of TGF-β could indicate better wound healing, whereas impaired TGF-β signaling has shown to delay wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non-diabetic wounds, the diabetic wound healing process has a prolonged the inflammatory stage, with the excessive secretion of inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin(IL)-1β, and IL-6. This leads to increased tissue damage, which delays diabetic wound healing by interfering with the proliferation and maturation stages ( 7 ). In long-term hyperglycemia, accumulated advanced glycation end products (AGEs) increase reactive oxygen species (ROS) production ( 8 ).…”
Section: Introductionmentioning
confidence: 99%